PSVII-2 Effects of Feeding a Starch or Pectin Supplement on Ruminal Parameters and gas Production of Grazing Young Bulls. (21st September 2022) - Berca, Andressa S Scholz; Cardoso, Abmael Silva; Fonseca, Natalia Vilas Boas; Reis, Ricardo Andrade; Tedeschi, Luis O
Abstract: The study aimed to investigate the effects of two feeding times and two sources of energy supplementation on pH, short-chain fatty acids (SCFA), and in vitro gas production (IVGP) of beef cattle reared in Urochloa brizantha cv. Marandu pastures. We used eight rumen-cannulated ½ Aberdeen Angus x ½ Nellore young bulls (280±7 kg) distributed in a double 4x4 Latin square design. Treatments consisted of supplementation at 0.3% of body weight with corn or citrus pulp, supplied at 0900 or 1700. Ruminal fluid pH was measured with a digital pH analyzer and SCFA was analyzed on a Shimadzu HPLC. The IVGP was determined using a transducer and a data logger for 48 h after incubation of samples combining forage and supplement in real intake proportion (88% forage, 12% supplement). Considering the rapid fermentation of sugars, animals supplemented with pectin maintained higher pH (P = 0.021) due to changes in bacterial populations to digest the pectic substances (Table 1). Lactate production after starch digestion caused lower pH. Despite the differences in evaluated energy substrates, there was no effect on the primary SCFA concentration (P > 0.05). Citrus pulp provided greater formic (P = 0.005) and valeric (P = 0.042) acids concentrations compared with corn, but there was no influence of formic acid in lactic acid production (Table 1). The greater IVGP by citrus pulp (P = 0.0140; Figure 1) may be related to its greater carbohydrate fraction A, soluble with a rapid rate of rumen degradation, and also because its ruminal fermentation results in greater acetic acid production, which provides more ruminal H2 and CO2, favoring the CH4 production. The citrus pulp can be used as an alternative source to corn because it might prevent acidosis, does not affect the main SCFA production, and is a non-human edible feed.